Aerobic exercise improve HbA1c levels and sensory outcome in diabetic peripheral neuropathy: A systematic review and meta-analysis - Jannah, Asyarotul; Bambang Purwanto; Wungu, Citrawati Dyah Kencono; Mohd Amin, Indah Binti; Hafizah Sururul Nur Rakhmawati; Saputra, Ketut Wahyu Adi (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Diabetic peripheral neuropathy (DPN) is one of the complications of type 1 and type 2 diabetes. Some parts of the body experience damage to the nerves due to high blood sugar levels. Aerobic exercise is known to improve glycaemic control and nerve function. This meta-analysis aimed to evaluate the effect of aerobic exercise on sensory and haemoglobin A1c (HbA1c) in patients with DPN. Methods: Literature searches were conducted in ScienceDirect, Pubmed, Web of Science, and Scopus for eligible articles published from 2010 to 2024. Inclusion criteria were determined using the PICOS approach with a moderate-intensity aerobic exercise intervention. The primary outcomes were sensory scores (sural and peroneal NCV) and HbA1c with a randomised control trial (RCT) research design. Results: We found that the pooled effect analysis of aerobic exercise on HbA1c of the three studies were significant (SMD -0.53; 95% CI = -0.89-0.17; P = 0.004) however there was no significant effect of non-physical activity/standard care on HbA1c (SMD 0.08; 95% CI = -0.26-0.42; P = 0.64). Meanwhile, analysis shows a moderate effect of aerobic exercise on NCV-sural examination scores with a pooled standardised mean difference (SMD) 1.40 (95% CI = 0.44-2.36). Conclusions: Our findings highlight aerobic exercise could be an effective non-pharmacological intervention to improve sural nerve function in DPN. Aerobic exercise regimens should be structured in a comprehensive therapy strategy. Further research is needed to focus on identifying the more optimal and tolerable aerobic exercise to maximise therapeutic approaches. In addition, there is a need to develop analyses of the effect of various intensities and types of exercise on DPN management.